FAKTOR-FAKTOR DETERMINAN PERAN DOSEN DALAM PENJAMINAN MUTU PERGURUAN TINGGI - Bambang Sumardjoko (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Determinant Factors of Lecturers Roles in Quality Assurance in HigherEducation. This study aims to (1) find out an empirically tested model ofdeterminant factors of lecturers roles in quality assurance in higher education, and(2) investigate contributions of leadership, organization culture, lecturerscompetence, and achievement motivation as individual variables and an aggregateto lecturers roles in quality assurance. The sample consisted of 206 lecturers ofprivate universities in the area of Surakarta, selected by the proportional randomtechnique. The data were collected through questionnaires and analyzed by theSEM technique. The results show that, first, the goodness of fit exists between theconceptual model and the empirically tested model (p-value 0.34 0.05 andRMSEA 0.01 0.05); second, the contributions of leadership, organization culture,lecturers competence, and achievement motivation to quality assurance are,respectively, 28.09%, 50.41%, 8.41%, and 5.29%; third, the contribution of thevariables as an aggregate is 95%. This implies that to improve lecturers roles inquality assurance in higher education, it is necessary to develop visionaryleadership, firm organization culture, competent lecturers support, and highachievement motivation.Keywords : leadership, organization culture, competence, achievement motivation,lecturers roles